Assessment of the feed additive consisting of Saccharomyces cerevisiae NCYC R404 for dairy cows for the renewal of its authorisation (Volac International Ltd) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of the authorisation of Saccharomyces cerevisiae NCYC R404 as a zootechnical additive (functional group: gut flora stabilisers) for dairy cows. The applicant has provided evidence that the additive currently on the market complies with the existing conditions of authorisation. There was no new evidence that would lead the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) to reconsider its previous conclusions on the safety of the product for the target species, consumers and the environment, for which the additive is considered to remain safe. Regarding user safety, the Panel reiterates its previous conclusions that the additive is not irritant to eyes and skin but should be considered a potential skin and respiratory sensitiser, and any exposure through skin and respiratory tract is considered a risk. There is no need for assessing the efficacy of the additive in the context of renewal of the authorisation.